Calculating the Universal Energy‐Level Alignment of Organic Molecules on Metal Oxides. (1st October 2012) - Ley, Lothar; Smets, Yaou; Pakes, Christopher I.; Ristein, Jürgen
Abstract Recently, Greiner et al. [Nat. Mater. 2012, 11, 76] published a survey of the level alignment of about 40 metal oxide/organic molecule interfaces. They observed a striking regularity in the electronic level alignment of the highest occupied molecular orbital (HOMO) and the Fermi level that depends solely on the difference between the substrate work function and the ionization energy of the molecule independent of the details of the electronic structure of the oxide. The authors could reproduce their data under the assumption of thermodynamic equilibrium occupation of the HOMO using four adjustable parameters. A model that quantifies well‐established concepts in heterojunction physics and achieves the same result without any adjustable parameters is presented here. This approach explains why the level alignment is rather independent of the experimental details, such as the electronic structure of the oxide, defects in the oxide, and the thickness of oxide and overlayer. The model can also be extended to organic molecules or polymers on metals without any intermediate oxide as long as certain conditions are met. It also sheds new light on the large polaronic binding energy required to interpret the electronic level alignment of metal‐polymer interfaces.